Gender, Age and Staff Preparedness to Adopt Internet Tools for Research Sharing During Covid-19 in African Varsities - Owan, Valentine, Joseph; Asuquo, Michael, Ekpenyong; Owan, Mercy, Valentine; Aslam, Sana; Obla, Moses, Eteng (My University, 2021)
This study assessed the partial as well as the collaborative impact of age and gender on academic staff preparedness to adopt Internet tools for research sharing in African universities during Covid-19. Although evidence abounds in the literature on gender and age as they affect relatively, scholars’ utilisation of digital tools for research communication, such studies did not examine scholars’ preparedness to adopt from a broad perspective of Africa. This study was conducted based on the argument that the preparedness of scholars may affect their future interest to utilize digital tools for research sharing. A quantitative method, based on the descriptive survey research design, was adopted to provide answers to four prevailing research questions. The examination focused on a populace of 8,591 staff in African universities, nonetheless, information was gathered from 1,977 of them, who deliberately took part from 24 African nations. A validated electronic rating scale, which was mailed/posted to targeted participants, was used as the instrument for data collection. Gender and age significantly affected academic staff preparedness to adopt Internet tools for research sharing partially and interactively in African Universities during Covid-19. Female staff were more prepared than males to adopt internet tools for research sharing during the pandemic. Older lecturers reported a higher rate of preparedness than their younger colleagues to adopt Internet tools for research sharing during Covid-19. In light of these proofs, ramifications and proposals for future exploration are discussed.
Keywords: Africa; Age; Covid-19; Gender; Internet tools; Research sharing